Analisis Strategi Kebijakan Pelayanan Publik Dalam Upaya Mempertahankan Predikat Wilayah Birokrasi Bersih Melayani pada Kantor Kementerian Agama Kota Denpasar - Putra, I Made Dwita (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
This Policy Paper analyzes the public service policy strategies at Kankemenag Kota Denpasar in its efforts to maintain its status as WBBM. The background of this policy paper is the urgency of maintaining the recognized quality of public services, considering internal and external challenges that can affect the consistency of WBBM standards. Although the designation has been achieved, issues regarding the sub-optimal nature of some public service aspects still frequently arise, indicating a gap between existing policies and their implementation on the ground, as well as the competency needs of human resources. This article employs a qualitative method with a descriptive-analytical approach. Primary data were obtained through in-depth interviews with leaders, service implementing staff, and representatives of the community service users. Meanwhile, secondary data were collected from internal documents related to service policies, performance reports, and applicable regulations. Data analysis was conducted thematically to identify patterns, challenges, and best practices in maintaining WBBM service standards. The article findings indicate that despite strong commitment and various policies being implemented, the lack of clear standardization for employee competency development through systematic training needs analysis (TNA) is one of the main obstacles. Adaptive and responsive human resource quality is a crucial pillar in maintaining the WBBM designation. Therefore, as a policy recommendation, this study proposes the issuance of a PMA or a KMA that explicitly mandates and standardizes the implementation of TNA across all work units within the Ministry of Religious Affairs, including Kankemenag Denpasar.